PARSITIPASI MASYARAKAT DALAM ADMINISTRASI KEPENDUDUKAN DI DISTRIK WAENGI KABUPATEN PUNCAK JAYA - WONDA, LEIRON; PANGKEY, MASJE; ROMPAS, WELSON (JURNAL ADMINISTRASI PUBLIK, 2019)
In the management and ownership of KK and KTP, the community members in Waengi District,Puncak Jaya Regency is still low. The purpose of this study was to determine community participation inpopulation administration in Waengi District, Puncak Jaya Regency.This study uses qualitative research to produce descriptive data in the form of words, data and observedbehaviors. This study is a qualitative study of one variable, community participation in populationadministration in Waengi District, Puncak Jaya Regency. In this research the parties that will be used asinformants are the informants who are chosen to obtain clear and accurate information in accordance withthe object to be examined. The procedure for taking the initial informants is then using the snowballtechnique, which is taking one person then being interviewed and then rolling to the other informants insequence in accordance with the informants that have been determined are representatives of the populationoffice, the District government, community leaders and local residents.Community awareness and spontaneous participation from the community for the ownership of a familycards and identity cards 30 percent of the Waengi district residents already have, while 70 percent of thepopulation does not yet have. the constraints experienced by the population are road, transportation,transportation financing, employment and the distance to place a family card and a low population identitycard at 13 percent, a population with a moderate participation rate of 7 percent, while there is no populationwith a high level of participation at distance is less than 300 kg. Residents with a distance of 309 m - 700 mwith a low participation rate of 23 percent, a population with a moderate participation rate of 20 percent,and residents with a high participation rate of 10 percent in the Waengi district of Puncak Jaya district.Keywords: Participation; Public; Administration; Population